(untitled) (Research, Society and Development, 2021)
This integrative review aims to present botanical, phytochemical and cytotoxic information about plant species commonly used. As a strategy to search for articles, the databases of Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO), Science Direct, and Google Scholar were used. selected works in Portuguese, English and Spanish. After reading the abstract, studies that met the requirements of the topic addressed were included. Works that, after reading in full, did not directly address the proposed theme were excluded. Records of the use of medicinal plants dating back to 1500 BC were observed. Associated with this, the "Green Pharmacopoeia", from 1926, was the first official Brazilian document with botanical descriptions of some medicinal plants. Concerning the families Moraceae, Asteraceae, Theaceae, Malvaceae, Junglandaceae, Celastraceae and Illiciaceae, the most abundant worldwide was the Asteraceae with about 1,600 genera and 23,000 species, while Theaceae, with about 10 genera and 195 species, was the least found . It was observed that the cytotoxicity assays, in vitro, both by direct and indirect methods, are configured as a tool to assess the toxicity of medicinal plants and some biological activities. In this context, in vitro cytotoxicity assays are a preliminary tool to assess the toxicity and biological activity of a medicinal plant.